(untitled) (International Journal of Biology and Chemistry, 2024)
Two solid (Double superphosphate and Phosphoric) and two liquid (Peat and Microfertilizer) fertilizers from Russia and Kazakhstan were evaluated with regard to macronutrients content (K, Ca), transition elements (Cr, Fe, Co, Zn, Hg), alkaline earth (Sr), semi-metals (As), rare earth elements (Ce, Eu, La, Nd, Sc, Sm, Tb, Yb) and Th and U. For analysis, the k0-INAA was used. For QA/QC purposes for k0-INAA the certified reference material BCR-320R channel sediment was used and irradiated together with the samples. The highest content of REEs was obtained in Double superphosphate, while in liquid fertilizers REEs were mostly below the limit of detection of the method used. Most elements in liquid organic fertilizers (Peat and Microfertilizer) were determined in insignificant level, except iron, which belongs to the essential micronutrients. The content of iron was at least 57 times higher in case of Peat fertilizer in comparison to Microfertilizer. Content of iron was higher in case of Phosphoric fertilizer than in Double superphosphate (about five times).